Feather mites (Acari: Astigmata) of captive Psittaciformes in Brazil - Pereira, D. M.; Hernandes, F. A. [UNESP]; Santos, A. C. G.; Nogueira, R. M. S. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2018)
Feather samples were obtained from the following Psittaciformes birds: Amazona amazonica, Amazona aestiva, Aratinga jandaya, Brotogeris spp., Ara ararauna and Ara chloropterus (total of 37 individuals). These birds were housed at the Wild Animal Screening Center of Maranhao, Sao Luis, Brazil. Four feathers were taken from the following regions: head, back, wings, belly/breast, thighs, and tail/covert. Mites were found on 17 birds (45.94%). Astigmatid mites belonging to the genera Fainalges (Xolalgidae), Chiasmalges (Psoroptoididae) and Tanyaralichus (Pterolichidae) were identified. The highest dominance coefficient was for the mite Fainalges sp. (DC= 96.29). Chiasmalges sp. was obtained only from Ara chloropterus, and Tanyaralichus was found in A. aestiva. The genus Fainalges was obtained from all the species of Psittaciformes studied, except for A. ararauna. In evaluating mite density according to body region, statistical differences were found between the back and wing regions (P= 0.041), back and thighs (P= 0.02), wings and tail (P= 0.002), belly and tail (P= 0.031) and thighs and tail (P= 0.001). The morphological variations observed in Fainalges spp. suggested the existence of three species that probably have not been described yet. This was the first record of the genus Tanyaralichus in Brazil.
Keywords: birds; acari; captive